Balancing between coordination, cooperation and competition? A mixed-method approach for assessing the role ambiguity of local sports authorities. Issue 3 (2nd July 2016) - Vos, Steven; Vandermeerschen, Hanne; Scheerder, Jeroen
ABSTRACT: In recent years, the subsidiarity principle has been underlined in Sport-for-All policies in countries such as Germany, Austria and Belgium. According to this organising principle, issues need to be handled by the lowest possible political and administrative level, and as close to the citizens as possible. The 2007 decree concerning Sport-for-All policies at the local level in Flanders (Belgium) clearly referred to this. It emphasised the decentralisation of the Sport for All policy, and highlighted the regulatory and coordinating role of local sports authorities. As a consequence, they may face conflicting roles of being coordinator, regulator and provider of mass sport at the local level. In this paper, a mixed-method approach is used to give a closer insight in the role perceptions of local sports authorities in Flanders, and their position towards private sport providers. The results show that local sports authorities consider the coordination and regulation of mass sport in their municipality as their primary task. Yet, it appears that private sport providers also perceive competition from local sports authorities. Moreover, a considerable number of the local sports authorities believe they can combine the roles of provider and coordinator. As there appears to be considerable goal ambiguity, it is necessary for local sports authorities to formulate clear goals. Referring to the principle of subsidiarity, it is argued that sports authorities should only intervene when (non-)profit sport providers are not able to achieve the desirable outcomes with regard to sport and the welfare agenda.